Best Answer

Related Post

Spread the word

Digg this post

Bookmark to delicious

Stumble the post

Add to your technorati favourite

Subscribes to this post

3 Comments Already

mygif
5aboob Said,
February 6th, 2011 @1:50 am  

x^2 – x + 1 = 0

[1 +- sqrt(1-4)] / 2 = 1/2 +- sqrt(3) i/2

mygif
beautyinthebuff Said,
February 6th, 2011 @2:37 am  

You start by moving x to the other side:

x^2 – x + 1 = 0

now:

A = coefficient in front of x^2 (which is 1)
B = coefficient in front of -x (which is -1)
C = 1

use these values in the quadratic formula

mygif
Republican man 12 Said,
February 6th, 2011 @3:23 am  

Okay Quadratic formula is fun we just learned in third grade today

kk

X^2-x+1=0
-b plus or minus Sqrt(b^2-4ac)
all over 2 a

so discriminant is -1^2 -4(1(1)
-3
1+- sqrt(-3)
over -2
(1+-isqrt(3))/-2

Leave Your Comments Below

Please Note: All comments will be hand modified by our authors so any unsuitable comments will be removed and you comments will be appreared after approved